The asymmetric synthesis of amino acids via electrophilic glycinates - Sinclair, Peter John, author; Williams, Robert M., advisor (Colorado State University. Libraries, 1987)
A new asymmetric synthesis of α-monosubstituted-α-amino acids using D- and L-erythro-4-benzy loxycarbonyl-5,6-diphenyl-2,3,5,6-tetrahydro-1,4-oxazin-2-ones 108 as amino acid templates is described. Bromination of 108 with NBS generates the key electrophilic glycinate 132 which couples with a variety of carbon nucleophiles with high diastereoselectivity to afford the amino acid precursors 134. Catalytic hydrogenation of homologated heterocycles 134 directly furnishes the zwitterionic α-amino acids in high enantiomeric excess. Dissolving metal reduction of 134 permits the preparation of unsaturated amino acids while use of erythro-4-t-butoxycarbonyl-5,6-diphenyl-2,3,5,6-tetrahydro-1,4-oxazin-2-one 160 allows the direct preparation of t-BOC protected α-amino acids. The synthetic approaches to a number of biologically interesting amino acids are described and mechanistic aspects of the coupling reaction are discussed.
Keywords: Amino acids -- Synthesis